The resurrection of sweet corn inbred SC11-2 using marker aided breeding for β-carotene - Saha, Iman; Rathinavel, Krishnakumar; Manoharan, Bharani; Adhimoolam, Karthikeyan; Sampathrajan, Vellaikumar; Rajasekaran, Ravikesavan; Muthurajan, Raveendran; Natesan, Senthil (Frontiers in Sustainable Food Systems, 2022)
Sweet corn has dominated the urban market due to its sweetness, tenderness, and ease of digestibility. It's import and export values have dramatically increased during the past 10 years as a fresh, processed, and preserved commodity. However, the commercially available sweet corns are deficient in β-carotene. In our study, we introgressed the favorable allele of crtRB1 (responsible for high β-carotene) into the recurrent sweet corn inbred SC11-2 from maize donor parent UMI1230β1+ to develop the β-carotene-rich sweet corn genotype by marker aided breeding. The crtRB1 3′TE InDel marker was utilized for foreground selection of favorable genotype. A total of 103 polymorphic SSR markers were employed for background selection, resulting in a 96% recovery of recurrent parent genome (RPG). We recorded high β-carotene content (9.878–10.645 μg/g) in the introgressed lines compared to the recurrent parent, SC11-2 (0.989 μg/g). The sugar content ranged from 18 to 19.10% and was on par with the recurrent parent (20.40%). These biofortified inbreds can be used as a donor in maize breeding programs to develop sweet corn genotypes with high β-carotene content.